2019
DOI: 10.3390/ijerph16234871
|View full text |Cite
|
Sign up to set email alerts
|

A Training Program to Enhance Disaster Preparedness of Group Companies in the Tokyo Metropolitan Area

Abstract: Many business continuity (BC) plans do not mention food and water for BC personnel. Moreover, the BC relies on the assumption that, during an emergency or crisis, employees’ basic needs and personal hygiene are satisfied. Although no one can engage in BC without these supplies, literature regarding companies’ disaster stocks for their employees is limited. We evaluated the current situation of companies’ stockpiles of food and other supplies and what their employees thought about them after participating in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Considering that over 27% of the Japanese population is now older than 65 years, it should be highly probable that the business enterprises will receive stranded elderly people in disaster events. The current issue requiring the utmost urgency is the lack of sufficient stock space [24]; thus, food stockpiles should be prepared according to the conditions of the weakest victims to make the most of it because the emergency rations targeting them are also applicable for healthy people [25]. It should be mandatory for the firm's risk management to prepare and prevent food-related health hazards, including direct ones like anaphylaxis shock due to allergic foods or secondary hazards like aspiration pneumonitis among older people [26].…”
Section: Quiz Score Improvementsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that over 27% of the Japanese population is now older than 65 years, it should be highly probable that the business enterprises will receive stranded elderly people in disaster events. The current issue requiring the utmost urgency is the lack of sufficient stock space [24]; thus, food stockpiles should be prepared according to the conditions of the weakest victims to make the most of it because the emergency rations targeting them are also applicable for healthy people [25]. It should be mandatory for the firm's risk management to prepare and prevent food-related health hazards, including direct ones like anaphylaxis shock due to allergic foods or secondary hazards like aspiration pneumonitis among older people [26].…”
Section: Quiz Score Improvementsmentioning
confidence: 99%
“…Through the simulation of the sleeping condition, we learned that the participants experienced difficulties in sleeping from noises like the snoring of others, as well as bodily discomfort from sleeping on the floor only with schlaf sheets. In the sleeping condition simulation, the previous study demonstrated the importance of the mattress [24]; it is essential in the mentally and physically stressful life of the disaster victims to secure bedding apparatus that is comfortable enough to ensure sound sleep. Even in the short training course of a two-day one-night period subjecting healthy participants, as we did in our study or in the previous study, the participants complained about discomfort in sleeping on the floor [24].…”
Section: Bedding Apparatus Stocked In the Facilitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, many studies believe that the residents’ preparedness for avoiding disasters is simply material preparation, which is measured from the perspective of residents’ material preparation. Among them, the most common way to measure disaster preparedness is to ask residents whether they have prepared emergency disaster kits (flashlights, radios, clean water) (e.g., [ 35 , 36 , 45 , 46 ]), buy insurance (e.g., [ 24 , 25 ]), if they had an escape plan (e.g., [ 39 , 40 , 41 , 42 , 47 , 48 ]) and reinforce houses (e.g., [ 38 , 49 ]). In addition, some scholars have noted that in addition to material preparation, residents’ disaster preparedness, conscious disaster risk management behavior is also an effective means to deal with disaster impact (e.g., [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%